2019
DOI: 10.4049/jimmunol.1800681
|View full text |Cite
|
Sign up to set email alerts
|

Different Isoforms of the Neuronal Guidance Molecule Slit2 Directly Cause Chemoattraction or Chemorepulsion of Human Neutrophils

Abstract: The movement of neutrophils between blood and tissues appears to be regulated by chemoattractants and chemorepellents. Compared to neutrophil chemoattractants, relatively little is known about neutrophil chemorepellents. Slit proteins are endogenously cleaved into a variety of N and C terminal fragments, and these fragments are neuronal chemorepellents and inhibit chemoattraction of many cell types, including neutrophils. In this report, we show that the 140 kDa N-terminal Slit2 fragment (Slit2-N) is a chemoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…In this study, SLIT2 increased the MVD and leucocyte/macrophage infiltration in PAPT. Pilling et al (2019) recently reported the SLIT2 isoform-specific neutrophil chemorepellent and chemoattractant functions. The ∼140-kDa N-terminal Slit2 fragment (Slit2-N) enhances, and the ∼110-kDa N-terminal Slit2 fragment (Slit2-S) inhibits neutrophil migration via binding with same ROBO1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SLIT2 increased the MVD and leucocyte/macrophage infiltration in PAPT. Pilling et al (2019) recently reported the SLIT2 isoform-specific neutrophil chemorepellent and chemoattractant functions. The ∼140-kDa N-terminal Slit2 fragment (Slit2-N) enhances, and the ∼110-kDa N-terminal Slit2 fragment (Slit2-S) inhibits neutrophil migration via binding with same ROBO1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a recent paper suggested that Slit2 can also cause chemorepulsion of human neutrophils other than chemoattraction 95. In their report, the authors showed that Slit2 comprises ∼140-kDa N-terminal Slit2 fragment (Slit2-N), which serves as a chemoattractant for human neutrophils, and ∼110-kDa N-terminal Slit2 fragment (Slit2-S), which serves as a chemorepellent for human neutrophis 95. They further found that the effects of both Slit2 fragments were blocked by Abs to the Slit2 receptor Roundabout homolog 1 or the Slit2 coreceptor Syndecan-4, but involved in different intracellular signaling pathways 95.…”
Section: Roles Of Slit/robo In Cell Motilitymentioning
confidence: 96%
“…On the contrary, a recent paper suggested that Slit2 can also cause chemorepulsion of human neutrophils other than chemoattraction 95. In their report, the authors showed that Slit2 comprises ∼140-kDa N-terminal Slit2 fragment (Slit2-N), which serves as a chemoattractant for human neutrophils, and ∼110-kDa N-terminal Slit2 fragment (Slit2-S), which serves as a chemorepellent for human neutrophis 95.…”
Section: Roles Of Slit/robo In Cell Motilitymentioning
confidence: 97%
See 1 more Smart Citation
“…One interesting property of the Slit ligands is that they can interact with different receptors by undergoing proteolytic processing [57]. For example, Slit2 is cleaved into N-terminal and C-terminal fragments, which differentially regulate the chemotactic behaviors of neutrophils via attractive and repulsive effects, respectively [58]. In the nervous system, the N-terminal Slit2 fragment interacts with APPs [59], the precursor of the beta-amyloid peptide which contributes to Alzheimer's disease.…”
Section: Other Axon Guidance Molecules Involved In Neuroinflammationmentioning
confidence: 99%